2020
DOI: 10.1021/acsomega.0c04601
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Drought-Tolerant and Susceptible Peanut (Arachis hypogaea L.) Genotypes in Response to Drought Stress

Abstract: Peanut is frequently constrained by extreme environmental conditions such as drought. To reveal the involvement of metabolites, TAG 24 (drought-tolerant) and JL 24 (drought-sensitive) peanut genotypes were investigated under control and 20% PEG 6000-mediated water scarcity conditions at the seedling stage. Samples were analyzed by gas chromatography–mass spectrometry (GC–MS) to identify untargeted metabolites and targeted metabolites, i.e., polyamines and polyphenols by high-performance liquid chromatography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 69 publications
1
30
0
Order By: Relevance
“…Simultaneously, Invertases (INVs) plays an important role in primary metabolism and plant development, which can hydrolyze sucrose into glucose and fructose (Ruan et al, 2010;Min et al, 2016) and contribute to osmotic adjustment under water deficit conditions (Konigshofer and Loppert, 2015). A similar result has shown that starch and sucrose metabolism was significantly affected by drought stress in peanut (Gundaraniya et al, 2020). These results showed genes involved in the regulation of starch and sucrose metabolism may play an important role in drought stress.…”
Section: Analysis Of Starch and Sucrose Metabolism In Response To Drought Stressmentioning
confidence: 83%
“…Simultaneously, Invertases (INVs) plays an important role in primary metabolism and plant development, which can hydrolyze sucrose into glucose and fructose (Ruan et al, 2010;Min et al, 2016) and contribute to osmotic adjustment under water deficit conditions (Konigshofer and Loppert, 2015). A similar result has shown that starch and sucrose metabolism was significantly affected by drought stress in peanut (Gundaraniya et al, 2020). These results showed genes involved in the regulation of starch and sucrose metabolism may play an important role in drought stress.…”
Section: Analysis Of Starch and Sucrose Metabolism In Response To Drought Stressmentioning
confidence: 83%
“…In response to water deficit, the enhanced biosynthesis of cinnamic acid in leaves was reported for tolerance in peanut [ 35 , 36 ] and tobacco [ 37 ]. These findings are in line with ours, which show that long-term drought resulted in a highly pronounced cinnamic acid content increase in the DT maize inbreds (from 85% in DT2 to 284% in DT3 to 432% in DT1).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sugars, the concentrations of nigrose, seduheptose and galactose were enhanced in DS, whereas glucose, fructose and galactose levels increased in DT. Similarly, in both leaves and roots of peanuts submitted to drought stress, metabolomics analysis showed that pentitol, phytol, xylonic acid, d-xylopyranose, stearic acid and D-ribose were important drought-response metabolites [33]. Agmatine and cadaverine were present only in DT during drought.…”
Section: Water Scarcity and Drought Stressmentioning
confidence: 99%
“…In the one-way designs, the stress variable has been evaluated at two (control vs. stress) or more (control and various levels of the stress factor) levels. For instance, the effect of drought stress in the host's metabolome has usually been evaluated using a control vs. stress design [32][33][34], whereas various salt concentrations have been used to assess the effect of salinity in the plant's metabolome [35,36]. In both cases, the studies have been balanced as the same number of individuals has been evaluated at each level of stress.…”
Section: Design Of Experimentsmentioning
confidence: 99%